2018
DOI: 10.1017/s1431927618012825
|View full text |Cite
|
Sign up to set email alerts
|

Synchrotron-based X-ray Fluorescence Microscopy as a Complementary Tool to Light Microscopy/Electron Microscopy for Multi-scale and Multi-modality Analysis

Abstract: Correlative microscopy allows us to identify sites-of-interest across different length scales and perform both structural and chemical analysis by combining the use of light, electrons and x-ray photons. It becomes an essential method to address questions for both biological and materials sciences. We have presented here example studies as well as the challenges of using synchrotronbased x-ray fluorescence microscopy (SXFM) as a complementary tool to either light microscopy (LM) or transmission electron micros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 5 publications
0
1
0
Order By: Relevance
“…X-ray Fluorescence Microscopy (XFM) 32 methods indicated that cortical vesicles in mouse eggs contain on average one million zinc ions each 3 and we employed this approach to test for the presence of analogous zinc- and manganese-enriched sites in small sections at the cortices of Xenopus eggs and embryos. To preserve transition metal contents in our samples we used a modified form of Timm’s silver staining.…”
Section: Resultsmentioning
confidence: 99%
“…X-ray Fluorescence Microscopy (XFM) 32 methods indicated that cortical vesicles in mouse eggs contain on average one million zinc ions each 3 and we employed this approach to test for the presence of analogous zinc- and manganese-enriched sites in small sections at the cortices of Xenopus eggs and embryos. To preserve transition metal contents in our samples we used a modified form of Timm’s silver staining.…”
Section: Resultsmentioning
confidence: 99%